The endosomal pathway and the Golgi complex are involved in the Infectious bursal disease virus life cycle. - Delgui, Laura Ruth (2013)
Infectious bursal disease virus (IBDV), a double-stranded RNA virus belonging to the Birnaviridae family, causes immunosuppression in chickens. In this study, we defined the localization of IBDV replication complexes based on colocalization analysis of VP3, the major protein component of IBDV ribonucleoproteins (RNPs). Our results indicate that VP3 localizes to vesicular structures bearing features of early and late endocytic compartments located in the juxtanuclear region. Interfering with the endocytic pathway with a dominant negative version of Rab5 after the internalization step leads to a reduction in virus titer. Triple-immunostaining studies between VP3, the viral RNA-dependent RNA polymerase VP1, and viral double-stranded RNA (dsRNA) showed a well-defined colocalization, indicating that the three critical components of the RNPs colocalize in the same structure, likely representing replication complexes. Interestingly, recombinant expressed VP3 also localizes to endosomes. Employing Golgi markers, we found that VP3-containing vesicles were closely associated with this organelle. Depolymerization of microtubules with nocodazole caused a profound change in VP3 localization, showing a punctate distribution scattered throughout the cytoplasm. However, these VP3-positive structures remained associated with Golgi ministacks. Similarly, brefeldin A (BFA) treatment led to a punctate distribution of VP3, scattered throughout the cytoplasm of infected cells. In addition, analysis of intra- and extracellular viral infective particles after BFA treatment of avian cells suggested a role for the Golgi complex in viral assembly. These results constitute the first study elucidating the localization of IBDV replication complexes (i.e., in endocytic compartments) and establishing a role for the Golgi apparatus in the assembly step of a birnavirus.